2016
DOI: 10.1093/ntr/ntw184
|View full text |Cite
|
Sign up to set email alerts
|

Smokers’ Perspectives on Texting for Tobacco Dependence Treatment: A Qualitative Analysis: Table 1.

Abstract: The major themes identified included the program being a valued source of external support that provided useful strategies to reduce tobacco use. Subjects were satisfied with the frequency, timing, and number of texts. Texting was perceived as feasible, acceptable, and helpful in smokers' attempts to abstain from tobacco. Suggestions to improve the program primarily concerned increasing customizable options and using simple, declarative sentences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Several themes fit well with findings from other qualitative studies of SMS text messaging for smoking cessation. For example, the personalization of SMS text messages was deemed to be important among young adult smokers [33], pregnant smokers [34], and a clinical sample of adult smokers recruited through an emergency department [35]. Quotations from the current sample echo those from smokers in other studies suggesting the importance of tailoring messages to individual schedules, preferences, and motivations [33,35].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several themes fit well with findings from other qualitative studies of SMS text messaging for smoking cessation. For example, the personalization of SMS text messages was deemed to be important among young adult smokers [33], pregnant smokers [34], and a clinical sample of adult smokers recruited through an emergency department [35]. Quotations from the current sample echo those from smokers in other studies suggesting the importance of tailoring messages to individual schedules, preferences, and motivations [33,35].…”
Section: Discussionmentioning
confidence: 98%
“…For example, the personalization of SMS text messages was deemed to be important among young adult smokers [33], pregnant smokers [34], and a clinical sample of adult smokers recruited through an emergency department [35]. Quotations from the current sample echo those from smokers in other studies suggesting the importance of tailoring messages to individual schedules, preferences, and motivations [33,35]. Giving participants more choice in the content and timing of messages may enhance their sense of control [33] and reduce the likelihood that people become frustrated or inconvenienced by the texts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SmokeFreeTXT employs a number of behavior change strategies, including feedback and monitoring, social support, and shaping knowledge [31]. Based on the qualitative data we collected during our pilot study [16], we offer participants in the current trial a choice of how many messages they receive per day (up to 2 messages or up to 4 messages per day) and the time of day they receive the first message. We also added 18 messages for participants presenting to the ED with specific chief complaints (cardiac, respiratory, or wound care) during the index visit.…”
Section: Methodsmentioning
confidence: 99%
“…The components of our intervention were: a brief adaptation of motivational interviewing (MI), called the Brief Negotiation Interview [14], initiation of nicotine replacement therapy (NRT) in the ED with provision of a 6-week supply of patches and gum, referral to the Connecticut State smokers’ telephone quitline (QL), provision of a smoking cessation brochure, and the provision of a booster phone call 3 days after enrollment [10]. Recent pilot studies conducted by our group showed the feasibility and potential efficacy of ED-initiated short-message-service (SMS) for tobacco dependence treatment [15,16]. …”
Section: Introductionmentioning
confidence: 99%